Diamonds and War State, Capital, and Labor in British-Ruled Palestine - De Vries, David (Berghahn Books, 2010)
Based on previously unexamined historical documents found in archives in Belgium, England, Israel, the Netherlands, and the United States, this book is the first in English to tell the story of the formation of one of the world's main strongholds of diamond production and trade in Palestine during the 1930s and 1940s. The history of the diamond-cutting industry, characterized by a long-standing Jewish presence, is discussed as a social history embedded in the international political economy of its times; the genesis of the industry in Palestine is placed on a broad continuum within the geographic and economic dislocations of Dutch, Belgian, and German diamond-cutting centers. In providing a micro-historical and interdisciplinary perspective, the story of the diamond industry in Mandate Palestine proposes a more nuanced picture of the uncritical approach to the strict boundaries of ethnic-based occupational communities.